(untitled) (Acta Academica: Critical views on society, culture and politics, 2010)
This article explores the themes of interaction and antithesis between Christian and non-Christian scholarship, as developed within Christian-reformational circles since the 1930s. It presents the “classical” models of the Dooyeweerdian and Vollenhovian schools, as well as the suggestions by Jacob Klapwijk and Nicholas Wolterstorff. It is argued that the Dooyeweerdian approach is similar to the Vollenhovian one but more explicit on the possibility of cooperation with non-Christian scholarship. The proposals by Klapwijk and Wolterstorff contain acceptable elements and some ideas that should be clarified and refined further.